The Effect of Problem-Based Learning on Concept Mastery and Scientific Attitudes of Fifth Grade Students - Nurwahidah Umar; Evi Ristiana; Rosleny Babo (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research was to describe the effect of problem-based learning on students' mastery of scientific concepts and attitudes. This type of research is a quasi experimental research with nonequivalent control group design. The population of this study were 50 students of class V SD Aisyiyah Muhammadiyah 3 Makassar. The sampling technique was carried out through saturated sampling. Data were collected through test, questionnaires, and observation techniques. Data were analyzed through descriptive and inferential analysis, namely the independent t test. The results showed that problem-based learning had a significant effect on the mastery of scientific concepts and attitudes of fifth grade students at SD Aisyiyah Muhammadiyah 3 Makassar.